Low LH Level on the Day of GnRH Agonist Trigger Is Associated With Reduced Ongoing Pregnancy and Live Birth Rates and Increased Early Miscarriage Rates Following IVF/ICSI Treatment and Fresh Embryo Transfer - Benmachiche, Abdelhamid; Benbouhedja, Sebti; Zoghmar, Abdelali; Humaidan, Peter (Frontiers in Endocrinology, 2019)
Objective: To examine the correlation between serum luteinizing hormone (LH) levels on the day of GnRH agonist (GnRH-a) trigger and reproductive outcomes following in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) treatment and fresh embryo transfer, and to identify a pre-trigger serum LH threshold which would be compatible with the most optimal cycle outcome. Design: This study is based on data from a previously published randomized controlled trial conducted from 2014 to 2016. Patients: A total of 322 participants were enrolled. Setting: Private IVF center. Intervention(s): GnRH-antagonist-based IVF cycles triggered with GnRH-a. For the purpose of the study, patients were stratified according to preovulatory LH quartiles (Q1-Q4). Main Outcome Measure(s): Ongoing pregnancy rates (OP), live birth rates (LB) and early pregnancy loss (EPL) rates. Results: The results of the present study showed increasing OP as well as LB rates and decreasing EPL rates with increasing pre-trigger serum LH levels, (P for trend < 0.06, 0.07, and 0.02) respectively. The absolute difference between the highest LH(Q4) and the lowest LH (Q1) group was 13.4%, 12.1%, and 12% in OP, LB, and EPL rates respectively. In multivariate regression analysis, a pre-trigger serum LH level of 1.60 mIU/ml was identified as a threshold below which reproductive outcomes decreased. The ROC curve values were statistically significant for OP, LB, and EPL; the AUC (95% CI) = [0.59 (0.50-0.63) P<0.04; 0.57 (0.50-0.63) P<0.05, and 0.60 (0.51-0.70) P< 0.04] respectively. A significant positive correlation was found on the day of GnRH-a trigger between serum LH, the number of follicles, serum P4, and serum E2, p < 0.03; P< 0.03; and p< 0.001 respectively. Conclusion: Low serum LH levels on the day of GnRH-a trigger is associated with reduced ongoing pregnancy and live birth rates and increased early miscarriage rates. Our findings suggest a lower threshold of serum LH values on the day of GnRH-a trigger necessary to optimize reproductive outcomes in fresh embryo transfer cycles.